Magnetically driven Bi2O3/BiOCl-based hybrid microrobots for photocatalytic water remediation. Issue 47 (14th October 2015) - Mushtaq, Fajer; Guerrero, Miguel; Sakar, Mahmut Selman; Hoop, Marcus; Lindo, André M.; Sort, Jordi; Chen, Xiangzhong; Nelson, Bradley J.; Pellicer, Eva; Pané, Salvador
Abstract : Hybrid microstructures consisting of a CoNi segment for wireless magnetic manipulation coupled to a Bi2 O3 /BiOCl segment are utilized for water remediation. Abstract : In this work, we have developed 3D hybrid microstructures consisting of a short ferromagnetic CoNi segment for wireless magnetic control, coupled to a photocatalytic Bi2 O3 /BiOCl segment for water remediation under UV-visible light. These hybrid microstructures (pillars and helices) were fabricated using 3D photolithography and template-assisted electrodeposition, followed by in situ creation of a Bi2 O3 /BiOCl heterojunction after oxidation of Bi. This heterojunction is not only active under a wider solar spectrum but also ensures sufficient charge separation and hence low electron–hole recombination rate. As a result, these hybrid microstructures were able to degrade rhodamine B dye with a 90% efficiency in 6 hours. On application of magnetic fields we were able to precisely control the structures and collect them for reuse. Cytotoxicity tests were performed on our hybrid structures and a 95% cell viability was reported showing that our structures are biocompatible.